Extracellular AMP Inhibits Pollen Tube Growth in Picea meyeri via Disrupted Calcium Gradient and Disorganized Microfilaments - Junhui Zhou; Haobo Yang; Yue Zhang; Yuan Cao; Yanping Jing (Plants)
Adenosine monophosphate (AMP) is a hydrolysis product of adenosine triphosphate (ATP) and adenosine diphosphate (ADP). In mammalian cells, extracellular AMP functions as a signaling molecule by binding to adenosine A1 receptors, thereby activating various intracellular signaling pathways. However, the role of extracellular AMP in plant cells remains largely unclear, and homologs of A1 receptors have not been identified. Our previous studies have demonstrated that extracellular ATP (eATP) is crucial for the normal germination and growth of Picea meyeri pollen tubes. In the present study, we observed that the exogenous addition of ATP to a pollen culture medium could be degraded into AMP and adenosine. Furthermore, the addition of AMP and adenosine to the culture medium was found to inhibit pollen germination and tube elongation. Notably, the addition of an AMP receptor inhibitor into the culture medium mitigated the inhibitory effects of AMP on pollen tube growth. Through intracellular staining for Ca2+ and microfilaments, we discovered that high concentrations of AMP disrupt the Ca2+ concentration gradient and impair microfilament organization, ultimately resulting in inhibited pollen tube elongation. In conclusion, we propose that extracellular AMP, as a hydrolysis product of eATP, also plays a significant role in regulating P. meyeri pollen germination and tube growth in vitro.